The lysosomal membrane protein Sidt2 is a vital regulator of mitochondrial quality control in skeletal muscle. Issue 4 (14th March 2021) - Wang, Lizhuo; Yu, Cui; Pei, Wenjun; Geng, Mengya; Zhang, Yao; Li, Zihui; Liang, Feiteng; Tan, Fengbiao; Du, Hui; Gao, Jialin
Abstract: The role of Sidt2 in the process of glucose and lipid metabolism has been recently reported. However, whether Sidt2 is involved in the metabolic regulation in skeletal muscle remains unknown. In this study, for the first time, using skeletal muscle‐selective Sidt2 knockout mice, we found that Sidt2 was vital for the quality control of mitochondria in mouse skeletal muscle. These mice showed significantly reduced muscle tolerance and structurally abnormal mitochondria. Deletion of the Sidt2 gene resulted in decreased expression of mitochondrial fusion protein 2 (Mfn2) and Dynamin‐related protein 1 (Drp1), as well as peroxisome proliferator‐activated receptor γ coactivator‐1 (PGC1‐α). In addition, the clearance of damaged mitochondria in skeletal muscle was inhibited upon Sidt2 deletion, which was caused by blockade of autophagy flow. Mechanistically, the fusion of autophagosomes and lysosomes was compromised in Sidt2 knockout skeletal muscle cells. In summary, the deletion of the Sidt2 gene not only interfered with the quality control of mitochondria, but also inhibited the clearance of mitochondria and caused the accumulation of a large number of damaged mitochondria, ultimately leading to the abnormal structure and function of skeletal muscle.